Observations of wave‐induced pore pressure gradients and bed level response on a surf zone sandbar. Issue 6 (26th June 2017) - Anderson, Dylan; Cox, Dan; Mieras, Ryan; Puleo, Jack A.; Hsu, Tian‐Jian
Abstract: Horizontal and vertical pressure gradients may be important physical mechanisms contributing to onshore sediment transport beneath steep, near‐breaking waves in the surf zone. A barred beach was constructed in a large‐scale laboratory wave flume with a fixed profile containing a mobile sediment layer on the crest of the sandbar. Horizontal and vertical pore pressure gradients were obtained by finite differences of measurements from an array of pressure transducers buried within the upper several centimeters of the bed. Colocated observations of erosion depth were made during asymmetric wave trials with wave heights between 0.10 and 0.98 m, consistently resulting in onshore sheet flow sediment transport. The pore pressure gradient vector within the bed exhibited temporal rotations during each wave cycle, directed predominantly upward under the trough and then rapidly rotating onshore and downward as the wavefront passed. The magnitude of the pore pressure gradient during each phase of rotation was correlated with local wave steepness and relative depth. Momentary bed failures as deep as 20 grain diameters were coincident with sharp increases in the onshore‐directed pore pressure gradients, but occurred at horizontal pressure gradients less than theoretical critical values for initiation of the motion for compact beds. An expression combining the effects of both horizontal and vertical pore pressure gradients with bed shear stress and soil stability is used to determine that failure of the bed is initiated at nonnegligible values of both forces. Plain Language Summary: The pressure gradient present within the seabed beneath breaking waves may be an important physical mechanism transporting sediment. A large‐scale laboratory was used to replicate realistic surfzone conditions in controlled tests, allowing for horizontal and vertical pressure gradient magnitudes and the resulting sediment bed response to be observed with precise instruments. Contrary to previous studies, the pore pressure gradient exhibited a range of values when erosion occurred, which indicates that erosion is the result of multiple physical mechanisms competing to secure or destabilize the sediment bed. The observations provide a better understanding of the forces acting within the sediment, and could improve parameters used in coastal sediment transport models to better predict coastal change. Key Points: First large‐scale experiment observing colocated pore pressure gradients and instantaneous erosion depths on a surf zone sandbar Momentary bed failures beneath asymmetric wavefronts did not occur at a universal critical horizontal pore pressure gradient Observations suggest bed failure is a function of horizontal and vertical pressure gradients (body forces) combined with shear stress